Antibacterial activity of green tea, Camellia sinensis and Granny Smith green apples extract against Staphylococcus aureus / Nurul Atiqah Ahmad Roslan - Ahmad Roslan, Nurul Atiqah (2019)
Staphylococcus aureus is a type of bacteria that have potential to cause skin infection to humans or animals. Green tea and green apples consist of antibacterial properties that can inhibit the growth of bacteria. The aims of this study are to measure the antimicrobial activity on differences concentration of green tea and green apples extract and to compare the effectiveness of antimicrobial activity between green tea and green apples. The results from this study showed that there is no zone of inhibitions produced from both green tea and green apple extracts. The comparison showed that the both green tea and green apple is ineffective towards bacteria S. aureus.